The effect of different fabrication techniques on porosity of cobalt-chromium cast removable partial denture farm works. - Fryad Mustafa Rasheed; Rizgar Mohammed Ameen Hasan (Erbil Dental Journal)
Background and Objective: Cobalt-chromium removable partial denture has been in use for years and despite of the advantages that cobalt-chromium provides, it has many disadvantages. In recent years with the development of dentistry science a cobalt-chromium removable partial denture is still used. The purpose of this study was to evaluate the overall porosity of conventional versus computer-aided design/computer-aided manufactured (CAD/CAM) and 3D-Printed removable partial denture (RPD) frameworks based on tests data analysis, and to evaluate the porosity of each technique’s fabrication of the RPD frameworks. Methods: Thirty ideal maxillary stone cast class II modification 1, divided in to three groups for construction of single palatal strap framework conventionally and digitally. For each group, removable partial dentures (chromium cobalt framework) were constructed conventionally and digitally. After finishing and polishing of the prosthesis, the porosity test was performed for each group and then compared to each other. Results: As for the porosity test, the number of defects after finishing and polishing, shows that there are significant differences between the three groups depending on the value of the (F-test) which is less than (P< 0.01), The maximuim mean result was shown by group III, while the minimum result was shown by group I. Conclusions: Within the limitations of this study, although both 3D-printing and CAD/CAM methods of framework fabrication revealed clinically acceptable adaptation, the conventional cast RPD groups revealed less overall porosity.